C-reactive protein in patients with aggressive periodontitis - Jaroslav Mysak; Stepan Podzimek; Jana Vasakova; Jiri Mazanek; Alex Vinsu; Jana Duskova (Elsevier, 2017)
Background/purpose: The aim of this study was to evaluate and compare the systemic levels of C-reactive protein (CRP) in peripheral blood samples of patients with aggressive periodontitis during the first twelve months of periodontal treatment, at exactly six month interval measurements, and compare them with clinical periodontal parameters. Materials and methods: All patients (N = 45) were examined prior to the initiation of periodontal treatment. Patients were divided into two groups GAgP (Generalised form of aggressive periodontitis, N = 23) and group LAgP (Localised form of aggressive periodontitis, N = 22). Control group (CON) included 60 individuals with healthy periodontium. The levels of CRP were determined in both groups GAgP and LAgP three times in 6 month intervals during the periodontal treatment. Results: CRP is a plasma protein that reflects the extent of the acute phase response to inflammation and is one of the markers of choice for monitoring this response. In our study, CRP levels decreased in course of periodontal treatment in both groups (GAgP and LAgP) in a similar way as bleeding on probing (BOP) and probing pocket depth (PPD) indices. Conclusion: Our study results showed that CRP levels, as well as bleeding on probing (BOP) and probing pocket depth (PPD), indices decreased in course of periodontal treatment in patients with generalised and localised aggressive periodontitis. Therefore this marker might be exploitable as a means to evaluate periodontal health in patients with aggressive periodontitis. Keywords: aggressive periodontitis, C-reactive protein, periodontal index, cardiovascular diseases